Pengaruh Motivasi Belajar terhadap Hasil Belajar Peserta Didik kelas III pada Mata Pelajaran Bahasa Inggris di Madrasah Ibtidaiyah - Yulyanti, Arista Furi Yulyanti; Malik, Rena Fadilah; Hafman, Anita (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2025)
In connection with the introduction of factors that influence the level of learningsuccess, It is essential to do this to help students achieve learning outcomes thebest. This time the researchers used the Normalized Gain (N-Gain) Test. score,where the results show that it produces an average N-gain score of 0.56, Basedon the criteria table above, it can be interpreted as 0.56 In this case, it can be saidthat there has been a high and effective improvement regarding the method ortreatment In this research, there was an increase in learning outcomes for students.Results The calculation of the significance test that has been obtained shows thatthe t count obtained amounts to 2,360 with a significance value of 0.009. t tablevalue from the study with many samples or N= 25 then you can calculate thedegree of freedom (df) which is equal to 23. With a level of 0.05 then thesignificance table value is 1.714. From the calculation results that have beenobtained, it shows that t calculate 2,360 > t table value of 1,714 and significancevalue of 0.009 < 0.05, then ????o is rejected, with It can be concluded that there is asignificant influence between learning motivation and the results students studyat Madrasah Ibtidaiyah Hidayatul Atfhal, Jonggol. Motivation is something thatis within the students, which is cultivated and instilled with a desire to carry outlearning activities well. This is where students need motivation to study